A comparison of the alexithymia, self-compassion and humour characteristics of the parents with mentally disabled and autistic children - AYDIN, AYDAN (ELSEVIER SCIENCE BV, 2015)
In this research study, the scores of parents with mentally disabled and autistic children in the alexithymia, self-compassion and humour styles scales are compared and their scores are investigated focusing on the diagnosis of their children variable. Based on the relational screening model, this research study involves 120 mothers and fathers having children diagnosed with alexithymia and autism. As a result of the study, it was found that the comparison of the fathers-mothers' total scores in the alexithymia, self-compassion and humour styles scales and their sub-scale scores revealed that the only difference is in the over-identification sub-dimension of the self-compassion scale; moreover, regarding the question whether the scale scores vary depending on the variable of the diagnosis of their children, it was found that there is no statistically significant difference in the scale scores considering this variable. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Mentally disabled; autistic children; alexithymia; self-compassion; humour characteristics; parents; PHENOTYPE; MOTHERS; DEPRESSION; RESPONSES; MOOD